High prognostic value of pre-allogeneic stem cell transplantation minimal residual disease detection by WT1 gene expression in AML transplanted in cytologic complete remission. (December 2017) - Candoni, Anna; De Marchi, Federico; Zannier, Maria Elena; Lazzarotto, Davide; Filì, Carla; Dubbini, Maria Vittoria; Rabassi, Nicholas; Toffoletti, Eleonora; Lau, Bonnie W.; Fanin, Renato
Highlights: MRD in AML has become one of the most important factors to determine prognosis and therapeutic choices. We analyzed the prognostic value of pre-SCT MRD, evaluated by WT1 expression. Cases with cCR and MRD-WT1 negativity pre-SCT have lower Relapse Rate and better OS. Pre-SCT WT1 expression is a powerful predictor of post-SCT outcome in AML undergoing SCT in cCR. Abstract: We analyzed the outcome of allogeneic stem cell transplantation (allo-SCT) in acute myeloid leukemia (AML) patients according to molecular Minimal Residual Disease (MRD) status prior to allo-SCT. MRD was assessed by the quantitative expression of the pan-leukemic marker Wilms' tumor (WT1) gene, according to the validated LeukemiaNet method. Between 2005 and 2016, 122 consecutive AML patients, WT1 positive at diagnosis, received allo-SCT in cytologic complete remission (cCR). The median age at SCT was 53 years (range 18–70). Quantitative analysis of WT1 gene expression (bone marrow samples) was available in all cases both at diagnosis (100% of samples overexpressed WT1 with a mean of 8607 ± 8187 copies/10 4 Abelson) and immediately before allo-SCT. Eighty one cases (66%) were MRD-WT1 negative (WT1 <250 copies) and 41/122 (44%) cases were MRD-WT1 positive (WT1 >250 copies) prior to allo-SCT. We evaluated post-SCT overall survival (OS), disease free survival (DFS) and relapse rate (RR), according to MRD-WT1 status pre-SCT. Both post-allo-SCT OS and DFS were significantly improved in patients who were MRD-WT1 negative at the time of SCT compared with those who were MRD-WT1 positive, with a median OS and DFS not reached in the MRD-WT1 negative group and 9 and 8 months, respectively, in the WT1 positive group (OS log-rank p < 0.0001; hazard ratio [HR] 3.9, 95% confidence interval [95% CI] 2.0–7.38; DFS log-rank p < 0.0001; HR 3.73, 95% CI 2.0–6.72). The RR after SCT was 15% (12/81) in pre-SCT MRD-WT1 negative cases and 44% (18/41) in MRD-WT1 positive cases (p = 0.00073). Univariate analysis showed that MRD-WT1 negativity pre-SCT and grade <2 acute GVHD were significant prognostic factors for improved OS and DFS. However multivariate analysis showed MRD-WT1 negativity pre-SCT was the only independent prognostic factor for improved OS and DFS. These data show that pre allo-SCT molecular MRD evaluation using WT1 expression is a powerful predictor of post allo-SCT outcomes in AML undergoing SCT in cCR. Patients with both cCR and MRD-WT1 negativity before SCT have a very good outcome with lower RR and improved OS. The pre allo-SCT MRD-WT1 stratification in AML is a valuable tool to identify patients at high risk of post-SCT relapse, and can influence conditioning regimen intensification and/or post-SCT preemptive strategies.